A case study of social processes in a novel «Predatory things of the century» by the Strugatsky brothers - Shamiakina, Mariya V. (Journal of the Belarusian State University. Sociology, 2019)
The paper investigates the image of the future created by Soviet science fiction writers Arkady and Boris Strugatsky in the novel «Predatory things of the century», published in 1964. Under the image of the future, the author of the work understands the whole, believable and aesthetically perfect artistic world created by the writer, artist or filmmaker, the events in which occur after a certain period of time after the creation of the work. The action of the story «Predatory things of the century» takes place in 2019, which makes it possible to analyze various trends in the development of technology, science and social sphere from the mid-twentieth century to the present day, to note significant events and inventions that led to the formation of our modern society. And also to identify what features of certain phenomena have ensured their existence in the reality of today, while other trends have been deadlocked. The special significance of the study of this work is attached to the fact that it describes humanity in the transition to the world of the utopian future, where most of the acute economic and social contradictions characteristic of both the society of the 1960s of the twentieth century and today will be solved. At the same time, Arkady and Boris Strugatsky focused special attention on the description of personal and social problems that have arisen in the developed consumer society, as well as on the place in the society of the future subcultures, obviously replaced the unified state ideology. The paper analyzes the examples of technological, social and cultural foresight. Such phenomena as the widespread use of secondary resources, synthetic food, the introduction of unmanned vehicles, a variety of phenomena in the field of culture and entertainment industry are confirmed in our day. The forecasts of Strugatsky regarding the evolution of society did not come true: the growth of general welfare, the disappearance of the property stratification, the emergence of new pedagogy.